Women survivors and their children born of wartime sexual violence in northern Uganda. (27th December 2017) - Atim, Teddy; Mazurana, Dyan; Marshak, Anastasia
Abstract : Girls and women who bear children owing to wartime sexual violence committed by armed actors face challenges in gaining acceptance on return to their families and societies. This study analyses the lives of women survivors and their children born of wartime sexual violence in Uganda. It draws on a population‐based survey of 1, 844 households in the Acholi and Lango sub‐regions of northern Uganda, as well as on in‐depth qualitative interviews conducted in 2014 and 2015 with 67 purposefully selected women survivors of wartime sexual violence. The study finds that: stigma is linked to broader gender discriminatory sociocultural norms and practices and changes under different circumstances; women's economic agency is essential to reducing stigma; households with members who suffered war‐related sexual violence experienced significantly higher rates of violence post conflict than did other households; and the passage of time is less of a determining factor in their acceptance and reintegration than previously thought.